ANALISIS EFEKTIVITAS BAZNAS DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Hendriko Kaputra; Zuwardi (Jurnal Ekonomi dan Bisnis, 2025)
This research was motivated by analyzing the effectiveness of BAZNAS in improving community welfare. As an official institution that manages zakat, infaq and alms, it has an important role in the redistribution of wealth and community empowerment. The aim of this research is to determine the effectiveness of BAZNAS in improving community welfare through Productive Zakat in Pasaman Regency. Evaluate the extent to which zakat funds managed by BAZNAS are effective in providing real benefits to people in need and in advancing their economy. The type of research used in this research is field research with a descriptive qualitative approach. The results of this research show that BAZNAS has demonstrated success in collecting and distributing zakat, with various empowerment programs that have had a positive impact on community welfare. However, several challenges such as the public's lack of understanding of the zakat mechanism and transparency in fund management still need to be overcome. This research recommends increasing transparency, strengthening empowerment programs, and intensifying outreach to optimize the effectiveness of BAZNAS. With these steps, it is hoped that BAZNAS can be more optimal in improving community welfare and strengthening its role as a zakat management institution in Pasaman Regency.